Biosimilars: potential implications for clinicians - Eleryan MG; Akhiyat S; Rengifo-Pardo M; Ehrlich A (Dove Medical Press, 2016)
Misty G Eleryan,1 Sophia Akhiyat,2 Monica Rengifo-Pardo,1 Alison Ehrlich,1,2 1Department of Dermatology, The George Washington Medical Faculty Associates, 2George Washington University School of Medicine & Health Sciences, Washington, DC, USA Abstract: With the expiration of patent protection for several biologics looming, the production of highly similar therapeutic agents has begun to emerge on the pharmaceutical market. These alternative drugs are referred to as biosimilars. Many anticipate that the introduction of these agents will result in a reduction in health care costs, which may create a more affordable biopharmaceutical market and also improve patient access. In contrast to generics, which are exact copies of their original products, biosimilars are not identical to their reference products. Due to concern about the safety and efficacy of biosimilars, separate regulatory approval pathways have been developed and implemented by several countries, including the US and Europe. Europe has led the way in acceptance of biosimilars into mainstream clinical practice. Biosimilars are not generic products and require extensive clinical and nonclinical bioequivalence studies before receiving marketing approval. Not only is there a lengthy developmental process, but also they will likely be required to have postmarketing surveillance and ongoing safety monitoring to keep track of issues that may arise, such as immunogenicity. Although US Food and Drug Administration approved the first biosimilar product in March 2015, physicians remain unfamiliar about their indications. Keywords: biologics, biopharmaceuticals, biomimics, biocopies, interchangeability, immunogenicity